Circ_HUWE1: a novel regulator of lipid accumulation, inflammation, and gut microbiota in atherosclerosis - Zulong Sheng; Yi Fan; Zhenjun Ji; Yanru He; Rui Zhang; Yuyu Yao; Genshan Ma (Cell & Bioscience)
Abstract Background Atherosclerosis (AS) is a chronic cardiovascular disease characterized by lipid accumulation and inflammation within arterial walls, leading to plaque formation and cardiovascular events. Circular RNAs (circRNAs) have emerged as key regulators in various diseases, but their role in AS remains poorly understood. This study investigates the protective role and underlying mechanism of circ_HUWE1 in lipid metabolism, macrophage infiltration, inflammation, and gut microbiota modulation in AS. Methods Circ_HUWE1 expression was evaluated in coronary artery disease (CAD) patients and in fecal samples from AS patients. An ApoE−/− mouse model of high-fat diet (HFD)-induced atherosclerosis was employed to assess functional role of circ_HUWE1. Circ_HUWE1 overexpression was induced via adeno-associated virus delivery, and the impact on lipid accumulation, macrophage infiltration, inflammation, and gut microbiota composition was analyzed. Vascular smooth muscle cells (VSMCs) were used for in vitro studies of circ_HUWE1 mechanism of action, including interactions with miR-143-3p and IGFBP5. Results Circ_HUWE1 expression was significantly downregulated in CAD patients, fecal samples of AS patients and in HFD-fed ApoE−/− mice. Circ_HUWE1 overexpression reduced lipid accumulation, plaque formation, and macrophage infiltration in ApoE−/− mice. Circ_HUWE1 also mitigated dyslipidemia by lowering serum levels of triglycerides (TG), total cholesterol (TC), and low-density lipoprotein (LDL) while increasing high-density lipoprotein (HDL) levels. Histological analyses showed attenuation of hepatocyte steatosis and adipose tissue enlargement in HFD-fed ApoE−/− mice. Additionally, circ_HUWE1 reduced proinflammatory cytokines and adhesion molecules, highlighting its anti-inflammatory properties. Furthermore, circ_HUWE1 also modulated the gut microbiota by restoring the abundance of beneficial gut bacteria, Faecalibacterium prausnitzii and Coprococcus comes, which correlated with reduced plaque burden. Mechanistically, circ_HUWE1 functioned as a competing endogenous RNA (ceRNA) by sponging miR-143-3p, thereby upregulating IGFBP5 expression. In vitro, circ_HUWE1 suppressed lipid accumulation and inflammation in VSMCs, effects that were reversed by miR-143-3p overexpression and IGFBP5 knockdown. Conclusion Our study demonstrates for the first time that circ-HUWE1 exerts a protective effect against atherosclerosis by regulating lipid metabolism, macrophage infiltration and inflammatory responses through the miR-143-3p/IGFBP5 axis and reshaping the gut microbiota. These findings suggest circ_HUWE1 as a potential therapeutic target for atherosclerosis treatment.